Deregulated Expression of Mitochondrial Proteins Mfn2 and Bcnl3L in Placentae from Sheep Somatic Cell Nuclear Transfer (SCNT) Conceptuses - Czernik, Marta (PLoS One, 2017)
In various animal species, the main cause of pregnancy loss in conceptuses obtained by somatic cell nuclear transfer (SCNT) are placental abnormalities. Most abnormalities described in SCNT pregnancies (such as placentomegaly, reduced vascularisation, hypoplasia of trophoblastic epithelium) suggest that placental cell degeneration may be triggered by mitochondrial failure. We hypothesized that placental abnormalities of clones obtained by SCNT are related to mitochondrial dysfunction. To test this, early SCNT and control (CTR, from pregnancies obtained by in vitro fertilization) placentae were collected from pregnant ewes (at day 20 and 22 of gestation) and subjected to morphological, mRNA and protein analysis. Here, we demonstrated swollen and fragmented mitochondria and low expression of mitofusin 2 (Mfn2), the protein which plays a crucial role in mitochondrial functionality, in SCNT early placentae. Furthermore, reduced expression of the Bcnl3L/Nix protein, which plays a crucial role in selective elimination of damaged mitochondria, was observed and reflected by the accumulation of numerous damaged mitochondria in SCNT placental cells. Likely, this accumulation of damaged organelles led to uncontrolled apoptosis in SCNT placentae, as demonstrated by the high number of apoptotic bodies, fragmented cytoplasm, condensed chromatin, lack of integrity of the nuclear membrane and the perturbed mRNA expression of apoptotic genes (BCL2 and BAX). In conclusion, our data indicate that deregulated expression of Mfn2 and Bcnl3L is responsible for placental abnormalities in SCNT conceptuses. Our results suggest that some nuclear genes, that are involved in the regulation of mitochondrial function, do not work well and consequently this influence the function of mitochondria.